2004
DOI: 10.1103/physrevlett.93.067401
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement between a Photon and a Quantum Well

Abstract: The lack of translational invariance perpendicular to the plane of a single quantum well causes equal probability for spontaneous emission to the left or right. Combining one emission path from the left and one from the right into a common detector leads to interference fringes for fundamentally indistinguishable paths corresponding to geometries where the same in-plane momentum is transferred to the quantum well. For all other paths, no interference is observed because of the entanglement between the photon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…For example, the correlated emission of single photons can be demonstrated by using quantum dots [6] and bound excitons in semiconductors [7]. Experiments with quantum wells [8] and quantum dots [9,10,11] also show the potential of semiconductors for the generation of entangled photons, which are of interest in quantum information processing.In order to properly describe the generation and/or propagation of nonclassical radiation through complex material systems such as semiconductor slabs, one has simultaneously to deal with both higher-order radiationfield correlation functions and many-particle quantum statistics of the material system. Within the frame of macroscopic quantum electrodynamics (QED), methods of describing the quantized electromagnetic field in linearly responding (dispersing and absorbing/amplifying) media have been developed, with special emphasis on quantum-noise effects [12,13,14,15,16,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the correlated emission of single photons can be demonstrated by using quantum dots [6] and bound excitons in semiconductors [7]. Experiments with quantum wells [8] and quantum dots [9,10,11] also show the potential of semiconductors for the generation of entangled photons, which are of interest in quantum information processing.In order to properly describe the generation and/or propagation of nonclassical radiation through complex material systems such as semiconductor slabs, one has simultaneously to deal with both higher-order radiationfield correlation functions and many-particle quantum statistics of the material system. Within the frame of macroscopic quantum electrodynamics (QED), methods of describing the quantized electromagnetic field in linearly responding (dispersing and absorbing/amplifying) media have been developed, with special emphasis on quantum-noise effects [12,13,14,15,16,17].…”
mentioning
confidence: 99%
“…For example, the correlated emission of single photons can be demonstrated by using quantum dots [6] and bound excitons in semiconductors [7]. Experiments with quantum wells [8] and quantum dots [9,10,11] also show the potential of semiconductors for the generation of entangled photons, which are of interest in quantum information processing.…”
mentioning
confidence: 99%
“…Experimentally, Hoyer et al [2] have shown recently that well-resolved interference fringes can be observed when the light emitted into different directions from a non-resonantly pumped ordered quantum well is brought together in the same detector. The interference pattern depends strongly on the emission directions determined by the photon wave vectors q and q 0 , which have projections q k and q 0 k in the plane of the quantum well.…”
Section: Introductionmentioning
confidence: 97%
“…The fringes vanish already for small differences between q k and q 0 k , corresponding to deviations of about two degrees of the emission angles. These experimental results have been explained within the framework of a densitymatrix theory [2], which describes quantum-optics of semiconductor heterostructures on a microscopic basis [3,4]. In this approach, the semiconductor electrons and holes are treated on the same level as the quanta of the electromagnetic field.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation